Proteolytic Processing of the Cyt1Ab1 Toxin Produced by Bacillus thuringiensis Subsp. Medellin. (2000)
Bacillus thuringiensis produces d-endotoxins that require proteolytic processing to become active. The activation of the B. thuringiensis subsp. medellin 28 kDa (Cyt1Ab1) cytolytic toxin by trypsin, chymotrypsin and gut extract from Culex quinquefasciatus larvae was analyzed. The Cyt1Ab1 toxin of B. thuringiensis subsp. medellin was processed by all proteases tested to fragments between 23 and 25 kDa, while processing of the Cyt1Aa1 toxin produce fragments between 22.5 and 24.5 kDa. The Cyt1Ab1 toxin was preferentially processed at the alkaline pH of 12. The in vitro proteolytic processing of the Cyt1Ab1 toxin by C. quinquefasciatus larvae midgut extract showed a 25 kDa fragment; a similar result was observed when the activation was performed in the in vivo experiments. The solubilized Cyt1Ab1 toxin and the protease resistant cores generated by in vitro processing showed hemolytic activity but not mosquitocidal activity. Amino terminal sequence of the C. quinquefasciatus gut extract resistant fragment indicated that the cutting site was located between Lys31 and Asp32, with a sequence DDPNEKNNHNS; while for the trypsin-resistant fragment the cutting site was determined between Leu29 and Arg30, and for the chymotrypsin-resistant fragment between Arg30 and Lys3